Clinically obscure venous malformation in the sub mandibular triangle: A rare presentation - Mamta Agrawal; Manish Kumar; Vikrant Agrawal (Elsevier, 2012)
Vascular lesions have been classified as hemangiomas or vascular malformations depending on the presence of cellular proliferation. These lesions have been known to cause significant morbidity and even mortality in both children and adults. Confusing nomenclature, relative rarity of these lesions, inappropriate diagnosis, lack of precise imaging studies and deficiency of multidisciplinary approach are some of the factors which result in ineffective treatment of such patients. Here, we report a rare case of venous vascular malformation presenting as a mass in the sub mandibular region with no clinical stigmata which was diagnosed with the help of various imaging techniques and subsequently treated by surgery.